Color Combination In A Suit And Its Effect On Human Psychology - Elmurodova Diligul Joseph Qizi; Mirziyodova Kamila Bahadir Qizi; Rahmatallah Umida Saydazimovna (Peerian Journals Publishing, 2024)
In this article you will learn what each color means? How do colors affect our emotional state? You will also learn what color psychology is and how color combinations are perceived in different cultures?
Keywords: psychology of color; research; perception; color